The Vulnerability of European Roma to the Socioeconomic Crisis Triggered by the COVID-19 Pandemic - Macías-León, María Almudena; Del Pino-Brunet, Natalia (MDPI, 2023)
The Roma are the most significant ethnic minority in the EU, subject to severe discrimination, social exclusion, and poverty. Due to their deplorable living conditions, isolation, and widespread antigypsyism, Roma are among the most affected by the socioeconomic crisis triggered by the COVID-19 pandemic. This article aims to assess the impact of this crisis on the Roma population from a multidimensional perspective. A thematic review of recent studies and reports on the pandemic’s effects on the Roma ethnic minority in Europe was carried out. In this work, the COVID-19 pandemic has been identified as a new global factor that influences the pre-existing exclusion dynamics and Roma mobility within Europe. Results show that these precarious living conditions have deteriorated to alarming levels in most European countries, leading to increased food insecurity and new forms of discrimination and stigmatization. The Roma ethnic minority has been disproportionately affected by mobility restrictions imposed by COVID-19. In all European nations, racist and xenophobic attitudes toward the Roma ethnic minority have increased during the socioeconomic and health crisis. The pandemic has intensified a process of ethnicization, fostering anti-Roma sentiment among the general population.
Keywords: Gitanos; Roma population; Covid-19; Antigypsism; Unequilities; Ethnicization